The Ongoing Battle over the Second Amendment: From Self-protection to Gun Control - Zerrouki ,Djilali; Kaid, Nassima (Faculty of Letters and Foreign Languages Department of English, 2017)
The present research will take a historical approach to the origins of the Second Amendment to the US Constitution and gun control in the United States. This research is divided into three Chapters. The first explores the origins of the Second Amendment. This section will show the historical background of the Second Amendment. The second section examines the ruling in Heller v. District of Colombia (2008) and how it addresses the right to self-defense, showing the effects that the case had on Americans. This part looks at the different developed nations compared to the U.S., to see if there is a correlation between the number of guns and homicides committed by firearms. Whether controlling guns would prevent mass shootings such as the one in Newtown remains a matter of debate. These sections will seek to assess the potential effects of modern US politics on the legality of gun control legislation in the face of increased violence in the 21st century